Brain Gain or Brain Waste? Horizontal, Vertical, and Full Job-Education Mismatch and Wage Progression among Skilled Immigrant Men in Canada. Issue 3 (September 2019) - Banerjee, Rupa; Verma, Anil; Zhang, Tingting
This study examines the incidence and wage effects of vertical, horizontal, and full job-education mismatch for high skilled immigrant and native-born men over a six-year period, using a Canadian longitudinal dataset. Immigrants (particularly racial minorities immigrants) are more likely to be fully mismatched than white native-born Canadians. Full mismatch lowers initial wages, especially for racial minority immigrants. Full mismatch accelerates immigrants' wage growth slightly over time, but this is not enough to narrow the immigrant wage gap over the six-year survey period. The results highlight the importance of disaggregating the different types of job-education mismatch experienced by immigrants.